CdTe colloidal-gel: Synthesis and thin films deposition applied to solar cells. (15th August 2021) - Arce-Plaza, Antonio; Sánchez-Rodríguez, F.J.; Courel, Maykel; Pérez-Cuapio, Rene; Alvarado, J.A.; Roque, J.; Ortega-López, M.
Abstract: A novel process of cadmium telluride (CdTe) synthesis and deposition applied in solar cells technology is presented in this research. Solar cells proposed; were manufactured using chemical deposition techniques, at low temperatures and without vacuum which let us reduce production costs. A configuration of Glass/SnO2:F/CdS/CdTe/Ag was chosen in order to assemble the photovoltaic device. As prior mentioned a simple Dr. Blade technique was used for CdTe thin films deposition (1.1 μm) in average thickness. These films were characterized by X-ray diffraction (XRD), photoluminescence (PL), scanning electron microscopy (SEM) and energy dispersion spectroscopy (EDX). The obtained results analysis demonstrated an enhanced property for photovoltaic devices applications. Thus the photovoltaic effect was studied by J-V analysis.